Antonio Pérez-Romero,«La Celestina and Inner Desire for Equality: The Search for Lasting Relationships as Existentialist Fulfillment». Capítulo en The Subversive Tradition ins Spanish Renaissance Writing. Lewisburg: Bucknell University Press, 2005 - Fernández, Enrique (Celestinesca, 2021)
N/A